Nutritional status in the pediatric oncology patients - Silvia Triarico; Emanuele Rinninella; Giorgio Attinà; Alberto Romano; Palma Maurizi; Stefano Mastrangelo; Antonio Ruggiero (Frontiers in Bioscience-Elite, 2022)
Nutritional status plays a vital role in the growth of children. In pediatric patients, disease-related malnutrition is a dynamic and multifactorial process supported by several factors such as inflammation, increased energy expenditure, decreased intake or reduced utilization of nutrients. In pediatric patients with malignancies, sarcopenia may coexist with malnutrition, amplifying its negative impact on prognosis. Careful monitoring of nutritional status both at diagnosis and during chemotherapy treatment allows early detection of the risk and/or presence of malnutrition. A rapid and personalized nutritional intervention can improve adherence to treatment, reduce complications and improve the patients’ quality of life.